Decline of Real Power Loss and Preservation of Voltage Stability by using Chirping Algorithm - Lenin Kanagasabai (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2015)
In this paper, a new Chirping Algorithm (CA) is developed based on the chirping behaviour of crickets for solving the reactive power optimization problem. It is based on the chirping behaviour of crickets (insect) found almost everywhere around the world. The proposed Chirping Algorithm (CA) has been tested in standard IEEE 30, 57,118 bus test systems and simulation results show clearly the better performance of the proposed algorithm in reducing the real power loss and control variables are well within the limits.